TANGGUNG JAWAB HUKUM ADVISING BANK DALAM PEMBAYARAN BARANG DENGAN MENGGUNAKAN “LETTER OF CREDIT” (Studi Pada The Development Bank of Singapore (Bank DBS) Jakarta) - SRI MAYA SARI (PREMISE LAW JURNAL, 2015)
Letter of Credit, a payment method in the export-import transaction which is considered as the safe one, in its implementation has some deviations and problems which cause an L/C not to run smoothly. This problem is closely related to the responsibility of the stakeholders that are involved in it. The problem of the research was how about the responsibility of advising bank in paying for goods by using letter of credit. The case occurred in The Development Bank of Singapore (DBS Bank), Jakarta. Here, the L/C transaction occurred between importer and exporter through their banks respectively. However, when the goods arrived at the importer’s warehouse, they were not matched with the ordered ones. The importer ordered coconut shell charcoal, but he received the charcoal waste. The importer then asked the Advising Bank to refund them. The research used judicial normative method. Secondary data were gathered by conducting library research and scrutinizing all legal provisions related to L/C, along with conducting interviews with source persons in order to get the information. The gathered data were analyzed qualitatively. The result of the research, concerning the responsibility of the Advising Bank, shows that the Bank could reject the refund for the L/C because it is only responsible for the things stipulated in Article 34 UCP 600, as long as the documents, in the front view, are in line with the explanation in the L/C documents. When there is a fraud as what occurs in the case above, the bank is not responsible for the form, completeness, originality, forgery, or legal consequences of any document or of the condition mentioned in the document or any addition in the document. The bank is not also responsible for the explanation, the amount, weight, quality, condition, packaging, delivery, value, or the content of the goods attached in the original document. Along with UCP 600, in Article 5, the responsibility of the Advising Bank is limited in the document matters, not in the content of the shipped goods. Keywords: Letter of Credit, Advising Bank